1996
DOI: 10.1016/0304-3959(95)00214-6
|View full text |Cite
|
Sign up to set email alerts
|

Gender variations in clinical pain experience

Abstract: This review is a critical summary of research examining gender variations in clinical pain experience. Gender-comparative pain research was identified through Medline and Psychlit searches and references obtained from bibliographies of pertinent papers and books. Review of this research demonstrates that women are more likely than men to experience a variety of recurrent pains. In addition, many women have moderate or severe pains from menstruation, pregnancy and childbirth. In most studies, women report more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

62
694
17
66

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,336 publications
(855 citation statements)
references
References 230 publications
62
694
17
66
Order By: Relevance
“…Also consistent with previous studies, correlates of needle fear included younger age and female sex [18,19]. We found that parents under-reported needle fear in their children when compared to children's self-report.…”
Section: Discussionsupporting
confidence: 91%
“…Also consistent with previous studies, correlates of needle fear included younger age and female sex [18,19]. We found that parents under-reported needle fear in their children when compared to children's self-report.…”
Section: Discussionsupporting
confidence: 91%
“…Di erent ways of expressing pain might have an impact on the choice of pharmacologial treatment, but in our study the di erences in choice of analgesics cannot be explained thus, since men and women described their pain very similarly. In the extensive review by Unruh in 1996 18 she declares that no evidence for gender di erences in the amounts of analgesics used has been found in non-SCI populations, but our ®ndings were in contrast to this. 53.8% of the women used one or more pain relieving drug compared to 27.7% of the men.…”
Section: Discussioncontrasting
confidence: 72%
“…25 In non-SCI populations, women often report more numerous pain locations than men 17,19 and more severe pain. 18 This was not the case in our study, where no di erences were found. But the greater prevalence of pain in women in our population of 456 individuals is supported by epidemiological studies of gender di erences in general.…”
Section: Discussioncontrasting
confidence: 62%
“…For example, some chronic diseases, including migraine, temporomandibular disorders, fibromyalgia, arthritis, and interstitial cystitis, are more prevalent in females [1,2]. Women usually display stronger pain perception and request more analgesics [3,4], while in pregnancy, increasing estrogen and progestogen have an anti-nociceptive role [5,6].…”
Section: Introductionmentioning
confidence: 99%